Effectiveness of Tutoring to Improve Academic Performance in Nursing Students at the University of Seville - María Dolores Guerra-Martín; Marta Lima-Serrano; Joaquín Salvador Lima-Rodríguez (Springer, 2017)
In response to the increase of Higher Education support provided to tutoring programs, this paper presents the design, implementation and evaluation of a tutoring program to improve the academic performance of at-risk students enrolled in the last year of a nursing degree characterized by academic failure (failed courses). A controlled experimental study was carried out to evaluate a tutoring program that included a minimum of nine meetings performed by an expert professor as tutor. A questionnaire for assessing the academic needs was designed and interventions were performed when responses were: nothing, a little or something. Medium to large effects were found in the progress of failed course to passed course (p =.000, rφ = .30), improving the information about courses (p < .001, d = 2.01), the information comprehension (p < .001, d = 0.85) and the strategies to improve academic performance (p < .001, d = 1.37). The intervention group students' response highlighted program satisfaction and effectiveness. The significance of the study lies in reinforcing the formal tutoring as a tool to improve academic performance in at-risk students.